Biogas production from residual marine macroalgae biomass: Kinetic modelling approach. (September 2022) - Pardilhó, Sara; Pires, José C.; Boaventura, Rui; Almeida, Manuel; Maia Dias, Joana
Graphical abstract: Highlights: Low-solids anaerobic digestion of marine macroalgae waste was conducted. Pseudo-first-order, logistics, modified, double and multi-Gompertz models were used. All models fit the experimental data with R 2 > 0.988. Multi-Gompertz fitting showed the highest R 2 and the lowest RMSE and AICc values. Abstract: Modelling the conversion of residual biomass to renewable fuels is of high relevance to promote the development of effective technological solutions. The present study compares the performance of five different kinetic models (pseudo-first-order kinetics, logistics, modified Gompertz, double-Gompertz, and multi-Gompertz) to describe the cumulative methane production during a low-solids anaerobic digestion of marine macroalgae waste. Different substrate concentrations were evaluated (0.9, 1.7 and 2.5% TS) with the best methane yield (105.2 mL CH4 .g VS −1 ) being obtained at the highest amount of biomass. All models fitted the experimental data with R 2 > 0.988. The innovative multi-Gompertz model herein proposed led to the best performance indexes for all tested experimental conditions, allowing to predict methane yields more accurately when the digestion occurs in two or more steps, as it was the case with marine macroalgae waste.